The Effect of Bevacizumab and Propranolol on Nasal Polyposis - Yuksel Olgun; Safiye Aktas; Semih Sutay; Mustafa Cenk Ecevit (International Journal of Clinical Practice)
Objective. This study aims to evaluate the effects of bevacizumab and propranolol from the point of view of a possible antiangiogenic effect in a model of primary nasal polyp (NP) tissue culture. Methods. NP samples of 21 patients and normal healthy nasal mucosa samples of 7 patients were cultured. Samples were divided into four groups as follows (healthy nasal mucosa, NP without any treatment, NP treated with propranolol, NP treated with bevacizumab). Cultured tissues were formalin fixed and paraffin embedded. Tissue sections and immunohistochemical VEGF-A, angiopoietin-1 (Ang-1), and angiopoietin-2 (Ang-2) expressions were evaluated. ELISA was also performed for each one of them. Results. Both propranolol and bevacizumab significantly decreased the expressions of VEGF-A and Ang-1, and they significantly increased the expression of Ang-2 in comparison to the control NP group. In the healthy nasal mucosa group, no significant expression of VEGF-A was seen, a slight (+) Ang-1 expression, and a high (+++) Ang-2 expression were observed. Conclusion. Bevacizumab and propranolol exert an antiangiogenic effect on NP tissues, mainly by decreasing VEGF-A and Ang-1 expression, increasing Ang-2 expression.